Eksperimen Pengembangan Produk Fungsional Bernilai Komersial Berbahan Baku Tempurung Kelapa Berusia Muda dengan Teknik Pelunakan - Dewi Pugersari; Achmad Syarief; Dwinita Larasati (Journal of Visual Art and Design, 2013)
Coconut shell, as coconut processing leftover, comes with unique characteristics, such as its strength, hardness, bending flexibility and also special texture of the surface. Those unique potentials and characteristics enable coconut shell to be used as craft materials. The objectives of this research are to find out the shell processing alternative technique and to know more about young age coconut shell's characteristics. The method used for this research is the material experiments and coconut shell as the craft materials, experiment of coconut shell utilization using generally known techniques, surface coloring technique, softening technique, reform technique with the help of base substance and experiment that refer to the unique characteristics of coconut shell.  According to the evaluation, it is concluded that coconut shell utilization using softening technique resulted in products that show less visual character and least natural compared to other techniques. Product that came out as the result with softening technique is still considered as the most suitable product which goes along with the contemporary style and owns the greatest unique value. It brings consideration that the softening technique- product has a great potential to be developed as other craft products. In addition, coconut shell used in softening technique is the young age shell which has not been used widely.